Current state and directions of development of bank lending to small and medium business in Ukraine - Харабара, Віолетта; Грешко, Роман Ігорович; Третякова, Олена Василівна (International Journal of Innovative Technologies in Economy, 2022)
The article analyzes the current trends in bank lending to small and mediumsized businesses in Ukraine and banking products and programs to help small and medium-sized businesses provided by individual state-owned banks. Conclusions on the current situation are substantiated and the directions of KEYWORDS development of bank lending to small and medium business are determined.
Keywords: small and medium business; micro-enterprises; banking institutions; bank lending; state support of small and medium business